2001
DOI: 10.1093/oxfordjournals.molbev.a003892
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Influence of Selection on the Variable Amino Acid Sites of the Cytochrome b Protein Functional Domains

Abstract: We evaluated the effects of selection on the molecular evolution of the functional domains of the mammalian cytochrome b gene as it relates to physicochemical properties shown to correlate with rates of amino acid replacement. Two groups of mammals were considered: pocket gophers of the rodent family Geomyidae, and cetaceans and ungulates of the monophyletic taxon Cetartopdactyla. Several characteristics of cytochrome b evolution were common to both mammal groups. The evolution of the matrix domain reflected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 30 publications
4
83
0
2
Order By: Relevance
“…TreeSAAP, in contrast, still showed evidence of significant (P < 0.01) destabilizing selection (n TS ) in almost all of the same gene regions, although at a lower level (Table 2). This difference again reaffirms the higher sensitivity of the evolutionary model of McClellan and McCracken (2001) for detecting adaptive selection. As reported before by Anisimova et al (2001Anisimova et al ( ,2002, both power and accuracy of the LRT and Bayes tests decrease as sample size diminishes, especially when the sequences are highly similar.…”
Section: Species Comparisonssupporting
confidence: 52%
See 2 more Smart Citations
“…TreeSAAP, in contrast, still showed evidence of significant (P < 0.01) destabilizing selection (n TS ) in almost all of the same gene regions, although at a lower level (Table 2). This difference again reaffirms the higher sensitivity of the evolutionary model of McClellan and McCracken (2001) for detecting adaptive selection. As reported before by Anisimova et al (2001Anisimova et al ( ,2002, both power and accuracy of the LRT and Bayes tests decrease as sample size diminishes, especially when the sequences are highly similar.…”
Section: Species Comparisonssupporting
confidence: 52%
“…Hence, in addition to estimating adaptive selection under codonsubstitution models M2, M3, and M8, we also estimated adaptive selection in terms of 31 quantitative biochemical properties using the model of McClellan and McCracken (2001) as implemented in TreeSAAP 3.2 (Woolley et al, 2003). No study has shown how tree topology and recombination affect the performance of the amino acid-property-based models implemented in Tree-SAAP.…”
Section: 23mentioning
confidence: 99%
See 1 more Smart Citation
“…A new family of methods recently has been proposed that approaches the question of amino acid replacement diagnosis using changes in physicochemical amino acid properties [6], [21], [11]. The use of amino acid properties results in a high degree of resolution that is more sensitive than the dN/dS approach [12], [16], and allows for the detailed diagnosis of individual amino acid changes in the context of the structure and function of proteins [1].…”
Section: Introductionmentioning
confidence: 99%
“…Substitution events are then inferred on each phylogenetic branch by directly comparing the hypothetical ancestral sequence at the basal end with the sequence at the terminal end. The ratio of inferred amino acid replacements to evolutionary pathways [11] is then calculated and used as a null hypothesis for the rate of random change for the sequence alignment. The overall pattern of inferred substitution is then compared to the distribution estimated using the null hypothesis to produce a series of z-scores to determine if certain magnitudes of change deviate from neutral expectations.…”
Section: Introductionmentioning
confidence: 99%